River basin trajectories : societies, environments and development - Molle, François; Wester, Philippus (Comprehensive assessment of water management in agriculture series, 2009)
This book contains 11 papers which cover a range of vital topics in the areas of water, agriculture, food security and ecosystems - the entire spectrum of developing and managing water in agriculture, from fully irrigated to fully rainfed lands. They are about people and society, why they decide to adopt certain practices and not others and, in particular, how water management can help poor people. They are about ecosystems - how agriculture affects ecosystems, the goods and services ecosystems provide for food security and how water can be managed to meet both food and environmental security objectives. This is the eighth book in the series.